The recent use of Swietenia mahagoni (L.) Jacq. as antidiabetes type 2 phytomedicine: A systematic review - Sukardiman; Ervina, Martha (Heliyon, 2020)
Natural resources provide more efficient and safer alternatives in managing diabetes compare to the synthetic oral anti diabetes (OAD). The plants not only have hypoglycemic effect, but also prevent its complications; in which no synthetic drugs provide of both properties. Among antidiabetes plants, mahogany seed (Swietenia macrophylla) has been used as traditional medicine in Indonesia and India, though most popular utilized as timber wood. The present study was performed of chemotaxonomic approach to review its phytochemical and anti-diabetic properties of Swietenia mahagoni (L.) Jacq seed/bark/leaves. The qualitative systematic review (SR) was carried out by analysing indexed journals and peer reviewed of Swietenia and Swietenia spp from Scopus, PubMed, Medline, Google Scholar, and Research Gate. Data selection criteria are accordance to botany, phytochemistry, in vitro, in vivo, and clinical test of related subject. The keywords used for the search in the databases were Swietenia, Swietenia mahagony, diabetes, and diabetes plants. Swietenia mahagoni (L.) Jacq. extracts have shown in vitro, in vivo and limited clinically test of its anti-diabetic properties. Ethanolic/methanolic/aqueous/petroleum/n-hexane extracts of mahagonis's seed/bark or leaves have anti-diabetic activities comparable to the synthetic drug and observed no to relatively mild toxic effect. The hypoglycemic mechanism suggested via reducing blood glucose level, restoring liver and β-cells islet function (might) blocking epinephrine function, inhibiting of α-amylase and β-glucosidase, antioxidant and antihiperlipidemia. Phytochemical compounds of S. mahagoni consist of the phenolics (flavonoids (swietemacrophyllanin, catechins and epichatechins) and tannins), triterpenoids and tetranortriterpenoids (limonoids: mahonin, secomahoganin, swietmanins, swiemahogins, swietenine and swietenolide), saponins and alkaloids which are known as anti-diabetic bioactive principles. S. mahagoni was potentially used and developed as an antidiabetes source. To use it as an antidiabetic further, more extensive clinical trials and biomarkers of active compounds determination are needed. Toxicology; Diabetes; Hypoglycemic; Mahogany; Meliaceae; Swietenia sp